2003
DOI: 10.1016/s0960-9822(03)00168-4
|View full text |Cite
|
Sign up to set email alerts
|

Eye Position Affects Activity in Primary Auditory Cortex of Primates

Abstract: Taken together with emerging results in both visual and other auditory areas, these findings suggest that neurons whose responses reflect complex interactions between stimulus position and eye position set the stage for the eventual convergence of auditory and visual information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
148
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 53 publications
14
148
3
Order By: Relevance
“…One or more tungsten electrodes were inserted just above the dura for the scan; these electrodes were readily visible in the images and served as reference points for the reconstruction of the recording locations. In accordance with the boundaries of the core auditory cortex identified in the literature (for details, see Werner-Reiss et al, 2003), we limited our recording locations to those Ն5 mm rostral from the caudal end of the supratemporal plane, Ն2 mm from the medial end of the supratemporal plane in the region caudal to the insula/circular sulcus, and Ն2 mm from the lateral edge of the supratemporal plane. In the region adjacent to the insula/circular sulcus, recording locations were restricted to those within the supratemporal plane rather than dipping down onto the lower/outer bank of the circular sulcus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One or more tungsten electrodes were inserted just above the dura for the scan; these electrodes were readily visible in the images and served as reference points for the reconstruction of the recording locations. In accordance with the boundaries of the core auditory cortex identified in the literature (for details, see Werner-Reiss et al, 2003), we limited our recording locations to those Ն5 mm rostral from the caudal end of the supratemporal plane, Ն2 mm from the medial end of the supratemporal plane in the region caudal to the insula/circular sulcus, and Ն2 mm from the lateral edge of the supratemporal plane. In the region adjacent to the insula/circular sulcus, recording locations were restricted to those within the supratemporal plane rather than dipping down onto the lower/outer bank of the circular sulcus.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for this design is that changes in eye position can produce changes in activity in auditory cortical neurons (Werner-Reiss et al, 2003;Fu et al, 2004;Woods et al, 2006). At the same time, visual stimuli can themselves influence the responses of auditory cortical neurons (Ghazanfar et al, 2005) as well as neurons in other areas of the auditory pathway (Porter et al, 2007).…”
Section: Does the Visual Fixation Stimulus Affect Auditory Spatial Sementioning
confidence: 99%
“…In congruent AV speech, subadditive interactions in polysensory regions have also been observed (32). Additionally, anatomical evidence shows that primary sensory areas are directly interconnected (33)(34)(35)(36)(37)(38). Intersensory corticocortical connectivity may mediate cross-modal plasticity when one sensory system is compromised (39), but the role for nonimpaired systems remains unknown.…”
Section: Neurophysiological Basis Of Multisensory Integrationmentioning
confidence: 99%
“…Factors other than attention can also influence activity of single neurons in the primary auditory cortex: various behavioral contingencies (Beaton and Miller, 1975;Miller et al, 1972), eye position (Fu et al, 2004;Werner-Reiss et al, 2003), and somatosensory stimulation (Brosch et al, 2005;Fu et al, 2003;Lakatos et al, 2007;Schroeder et al, 2001). …”
Section: Beyond Sound In Auditory Cortexmentioning
confidence: 99%
“…However, even some of the early studies suggested that neural activity in early stages of auditory processing might be influenced by nonauditory factors; such as "attention" influencing "electric activity" in the cochlear nucleus (Hernandez-Peon et al, 1956), and "attention units" in auditory cortex (Hubel et al, 1959). Since then, multiple studies supported the idea of multisensory, or behavioral interactions in auditory cortex, whether they were using evoked potentials (Giard and Peronnet, 1999;Oatman, 1971Oatman, , 1976Picton et al, 1971), field potentials (Ghazanfar et al, 2005), magnetoencefalography (Gobbelé et al, 2003;Lütkenhöner et al, 2002), or fMRI (Calvert et al, 1997;Foxe et al, 2002;Johnson and Zatorre, 2005;Kayser et al, 2005;Petkov et al, 2004) Even at the level of single neurons in the primary auditory area, neuronal responses can be influenced by behavioral contingencies (Beaton and Miller, 1975;Miller et al, 1972), selective attention Miller et al, 1980), eye position (Fu et al, 2004;Werner-Reiss et al, 2003), or somatosensory stimulation (Brosch et al, 2005;Fu et al, 2003;Lakatos et al, 2007;Schroeder et al, 2001). The "top-down" (attention, behavioral contingencies), and "bottom-up" (somatosensory, eye movements) influences can be seen as enhancing auditory responses, and auditory processing (Lakatos et al, 2007;Schroeder and Foxe, 2005).…”
Section: Nonauditory Modulation Of Activity In Auditory Cortexmentioning
confidence: 99%